KEABSAHAN PENERBITAN SURAT PENETAPAN KEMBALI TANPA SURAT PENETAPAN SEBELUMNYA - Aryo Hatmoko (UNES Law Review, 2023)
The purpose of this study is to analyze the validity of the SPKTNP without the SPTNP which has been regulated in the Customs Law which underlies the decision of the Supreme Court. The research is descriptive-analytical with a normative juridical approach. Collecting data by library or document study conducted by searching and studying and making an inventory of secondary legal documents or materials. As a result, the validity of the issuance of SPKTNP without SPTNP is regulated in Law Number 10 of 1995 Article 16 and its explanation which is closely related to Law Number 17 of 2006 Article 17 which is a re-stipulation. However, Article 16 paragraph (4) concerning the amount of the fine jo. Article 17 paragraph (4) which adds a fine from the construction of state administrative law is a positive fictitious decision considering that the function of government is active. Issuance of SPKTNP without SPTNP is a state administrative decision by Law Number 5 of 1986 concerning Administrative Court Article 1 point 3 jis Law Number 51 of 2009 concerning Amendments to Law Number 5 of 1986 concerning Administrative Court Article 1 point 9. The re-stipulation decision by the Supreme Court requires the issuance of the SPTNP before the issuance of the SPKTNP, then the Supreme Court did not defend the issuance of the SPKTNP without being preceded by the issuance of the SPTNP because it contradicted Article 17 jo. Article 16 of Law Number 17 of 2006 in conjunction with Article 7 of Law Number 12 of 2011 concerning the Establishment of Legislation.